The effectiveness of limited time systems promotional tools in enhancing awareness in unit trust investment scheme for City Unit Trust Bhd / Mohd Amirulfazli Ibrahim - Ibrahim, Mohd Amirulfazli (Faculty of Business and Management, 2005)
In this modern day business environment, the business world is getting more competitive and aggressive by the day. Businesses compete with each other in order to boost sales by trying to come up with the best advertisement and promotion by using all tools available. Since being introduced to the public, unit trust schemes are fast being one of the favorite investments by Malaysian and these causes the unit trust companies to come up with ways to attract potential investors. However, because of the regulations set by the governing board (Security Commission), the promotion done is limited even with the tools being readily available. Therefore, the objective of this study is (1) How effective are the limited promotion tools used by KL City Unit Trust Bhd , (2) What circumstances that may assist in creating awareness among customers? and (3) What are the expectations of customers toward products offer by KL City Unit Trust Bhd? This paper consists of 5 chapters which explain the subject matter in stages. Chapter 1 explains the introduction and background of the study. Chapter 2 explains the literature review, which relates to the subject studied and theoretical framework which act as a guide to the research flow and process. For chapter 3, research methodology is explained, which consist of methods and sampling techniques be used. Data findings and discussions is explained in chapter 4, derived from the information obtain from respondents. And finally, chapter 5 contain summary of results and findings, which explain conclusions and recommendations.